(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Purpose of the study is to identify, theoretically substantiate, and experimentally test the pedagogical conditions for developing professional-pedagogical competence in future teachers of visual arts based on a polyartistic approach